Kikuchi-Fujimoto disease complicated by aseptic meningitis and hemophagocytosis successfully treated with intrathecal dexamethasone. Issue 6 (June 2020) - Huang, Xiaoyan; Chen, Xixi; Tong, Sun-Wing; Wang, Yan; Cai, Jifu; Deng, Chaowen; Zhang, Lijun
Abstract: Kikuchi-Fujimoto disease (KFD) is thought to be a self-limited disease featuring fever and cervical lymphadenopathy; most cases having a favorable outcome. Severe disease and death are occasionally reported. Here we report a case of KFD complicated by hemophagocytosis and aseptic meningitis. The symptoms and laboratory parameters improved after systemic glucocorticoids, intravenous immunoglobulin and one dose of intrathecal dexamethasone. Clinicians should aware of this disease and make early diagnosis by lymph node biopsy to avoid over-treatment. Abstract : Diagnostics; Drug delivery; Emergency medicine; Hematological system; Immune system; Internal medicine; Medical microbiology; Neurology; Pathology; Kikuchi-fujimoto disease, Necrotizing lymphadenitis, Hemophagocytosis, Aseptic meningitis, Intrathecal injection